Sulfite Oxidation Mediated by Ortho-Phenylenediamine / Co(Ii)- Tetrakis(Para-Aminophenyl)Porphyrin Copolymers in Acid Medium - Aguirre-Quintana, M; Aguirre-Quintana, M; Romero-Figueroa, J; Herrera-Diaz, F; Herrera-Diaz, F; Arce-Escobar, R; Arce-Escobar, R; Márquez-Mandiola, P; Márquez-Mandiola, P (Sociedad Chilena de Quimica, 2013)
ABSTRACT The aim of this work is to study the sulfite oxidation mediated by glassy carbon electrodes modified with copolymers formed by ortho-phenylenediamine (OPD) and Co(II)-tetrakis(para-aminophenyl)porphyrin (CoTAPP). The copolymer was obtained through continuous cycling of potential of a glassy carbon electrode in acid medium containing each respective homopolymer in 1:1 feeding volume, in which the ortho-phenylenediamine concentration was 110-1 M and the CoTAPP concentration was 110-4 M. The film obtained is thin, stable and contains a low amount of porphyrin in comparison to the amount in ortho-phenylenediamine. Its electrocatalytic activity was tested toward the sulfite oxidation. In this case, this film is more electrocatalytic than the modified electrode modified with the CoTAPP electropolymer, even though ortho-phenylenediamine is inactive in this reaction. In this work the electrocatalysis process, the morphology of the film, and the difference of electrocatalytic behavior between the ortho-phenylenediamine and cobalt porphyrin homopolymers and the ortho-phenylenediamine-porphyrin copolymer were studied. The morphologic studies were done using Au electrodes since the electrocatalytic activity on Au and on glassy carbon are quite similar.